Dimensional Variations of Left-Sided Double-Lumen Endobronchial Tubes. (24th September 2019) - Hegland, Niels; Schnitzler, Sebastian; Ellensohn, Jan; Steurer, Marc P.; Weiss, Markus; Dullenkopf, Alexander
Abstract : Background . Tube size selection is critical in ventilating patients' lungs using double-lumen endobronchial tubes (DLTs). Little information about relevant parameters is readily available from manufacturers. The aim of this study is to provide reference data for relevant dimensions of conventionally available DLTs. Methods . In this study in a benchmark in vitro setup, several dimensional parameters of four sizes of left-sided double-lumen endobronchial tubes from six different manufacturers were assessed, such as distances and diameters of tube shaft, cuff lengths, and diameters as well the angle at the tip. Results . Endobronchial tubes of ostensibly the same size revealed wide variation in measured parameters between brands from different manufacturers. In some parameters, there was an overlap between different sizes from the same manufacturer, i.e., diameters and distances did not increase with increasing nominal endobronchial tube size. The information about dimensions of endobronchial tubes provided by manufacturers' leaflets is insufficient. Conclusions . Endobronchial tube size selection carries unnecessary uncertainty because clinically relevant parameters are unknown and vary considerably between different manufacturers.